1984
DOI: 10.1093/jn/114.4.719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Linoleate and Arachidonate Deficiencies on Reproduction and Spermatogenesis in the Cat

Abstract: The inability of the cat to convert significant quantities of linoleate [18:2(9,12)] to arachidonate [20:4(5,8,11,14]) in the liver makes the cat a useful model for studying the specific physiological roles of these two fatty acids. In these studies, cats were fed purified diets that were either deficient in essential fatty acids (EFAs) or that provided linoleate with or without arachidonate. Male cats that were fed the EFA-deficient diet for approximately 2 years exhibited extensive degeneration of the testes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 21 publications
2
25
1
Order By: Relevance
“…Because HSL catalyzes the hydrolysis of cholesterol ester and triacylglycerol, it is reasonable to speculate that cholesterol or fatty acids released by the action of HSL are required for spermatogenesis. In this concern, it is noteworthy that cholesterol contents of sperms are significantly altered during epididymal maturation (31) and that deficiency of essential fatty acids leads to extensive testicular degeneration (32). It is also possible that the male sterility arises from a disturbance of retinoid metabolism, since HSL mediates retinol ester hydrolysis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Because HSL catalyzes the hydrolysis of cholesterol ester and triacylglycerol, it is reasonable to speculate that cholesterol or fatty acids released by the action of HSL are required for spermatogenesis. In this concern, it is noteworthy that cholesterol contents of sperms are significantly altered during epididymal maturation (31) and that deficiency of essential fatty acids leads to extensive testicular degeneration (32). It is also possible that the male sterility arises from a disturbance of retinoid metabolism, since HSL mediates retinol ester hydrolysis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction in male cats appears normal when given an all-vegetable-fat diet devoid of arachidonate (MacDonald et al 1984;JG Morris, unpublished results). The testes of toms receiving a linoleate-containing diet had higher levels of arachidonate (indicating synthesis) than in the testes of cats given a linoleate-free diet.…”
Section: Essential Fatty Acidsmentioning
confidence: 93%
“…mal maturation (9). Moreover, pathological states of fatty acid deficiency have been identified that result in testicular degeneration and sterility (10). Thus, a suggested role for cholesterol ester hydrolysis in spermatogenesis is now conclusively demonstrated with the HSL knockout.…”
Section: Hormone-sensitive Lipase Plays a Critical Rolementioning
confidence: 99%